Preferensi Pemijahan dan Habitat Ikan Nomei (Harpodon nehereus) di Perairan Juata Laut Tarakan Sebagai Upaya Konservasi - Endik Deni Nugroho; Vlorensius Vlorensius; Adelyn Salurapa (Biogenesis: Jurnal Ilmiah Biologi, 2017)
Nomei fish (Harpodon nehereus) is a local marine fish found in the territorial waters of Tarakan. This fish is a commercial fish that is widely marketed in dry form, so the fish Nomei become one of the specialties foods of Tarakan. Continuous Nomei fishing will have an impact on the fishermen's incomes that begin to fall and the extinction of these fish in ecosystem habitats. One effort that can be done to preserve the existence of Nomei fish is the basic research related to habitat and Nomei spawning preference that founded in coastal areas of Tarakan, North Kalimantan. The benefits of this research are as a reference in the determination of Nomei spawning habitat based on breeding preferences of Nomei, also as the basis of management and conservation of Nomei declining as well as efforts to conserve local marine fish of Tarakan. This research type is descriptive qualitative, with survey approach. Descriptive qualitative, explaining Nomei spawning preferences based on fish habitat types. The use of descriptive type is expected to determine the spawning preference and the dispersal habitat type of Nomei. Data collection is also inseparable from the source (fishermen) through interviews.